Answer :

To Prove:

Taking LHS,


= cosx cos2x cos4x cos8x


Multiply and divide by 2sinx, we get




[ sin 2x = 2 sinx cosx]


Multiply and divide by 2, we get



We know that,


sin 2x = 2 sinx cosx


Replacing x by 2x, we get


sin 2(2x) = 2 sin(2x) cos(2x)


or sin 4x = 2 sin 2x cos 2x



Multiply and divide by 2, we get



We know that,


sin 2x = 2 sinx cosx


Replacing x by 4x, we get


sin 2(4x) = 2 sin(4x) cos(4x)


or sin 8x = 2 sin 4x cos 4x



Multiply and divide by 2, we get



We know that,


sin 2x = 2 sinx cosx


Replacing x by 8x, we get


sin 2(8x) = 2 sin(8x) cos(8x)


or sin 16x = 2 sin 8x cos 8x



= RHS


LHS = RHS


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Mark the Correct RD Sharma - Mathematics

Mark the Correct RD Sharma - Mathematics